Comparative Studies of Types of Nutritional Education Media, Consumption Behavior and Nutritional Status in Undergraduate Students and Employees of Chaiyaphum Rajabhat University - Kanthong, Pattira; Laklab, Chainarong; Wongsiri , Thimaporn; Mokpa, Peangpak; Pimol, Tipwarin (Journal of The Royal Thai Army Nurses, 2021)
From a study of 215 students and employee of Chaiyaphum Rajabhat University, the highest channel to receive nutrition education media was the Internet, accounting for 31.2 percent, followed by television, public relations boards, newspapers, magazines, brochures, radio, personal media and other media. The students had a normal weight of 66.2 percent, followed by being overweight, thin and very thin, 16.2%, 13.2%, and 4.4% respectively, while the staff members had a normal weight of 81.5 percent, followed by those who were overweight, very thin and thin, 7.4,% 7.4% and 3.7% respectively. The media that is most popular among males is television, accounting for 35.4 percent, while the most popular media for female is public relations boards with mean of media channels received between males was significantly different from that of females (p < .01). Among students the ages range of 18-19 years was significantly different from the age range of 22-23 years. However, the median channels received between the personnel of each age group were not significantly different from each other. In addition, the channels of nutrition education media with the level of health literacy and the nutritional status score no relationship by Pearson’s coefficient was at the .000 (p < .01), however only a slightly positive correlation was found in the health literacy level with the nutritional status score by Pearson’s coefficient was at .326 (p < .01), with the highest health literacy score among the samples who consumed the signboard media. 32.35 percent followed by television, internet, brochures, magazines, individual media, newspapers and community radio, which were 26.47, 24.51, 6.37, 3.43, .49 and .49, respectively.